2018
DOI: 10.1186/s12951-018-0393-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanosensors based on polymer vesicles and planar membranes: a short review

Abstract: This review aims to summarize the advance in the field of nanosensors based on two particular materials: polymer vesicles (polymersomes) and polymer planar membranes. These two types of polymer-based structural arrangements have been shown to be efficient in the production of sensors as their features allow to adapt to different environment but also to increase the sensitivity and the selectivity of the sensing device. Polymersomes and planar polymer membranes offer a platform of choice for a wide range of che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 62 publications
(74 reference statements)
0
31
0
Order By: Relevance
“…Subsequently, this scaling relationship was generally confirmed in a number of experimental studies and theoretical models [10][11][12][13][14][15], although there was no agreement on the value of power-law exponent (α). The predicted α=0.33 was found [10] to be a reasonable approximation for thin films (L=100 μ), while for the thicker films (L>100 μ) α≈0.5 [9] or even α≈1 [15] were obtained. These studies also confirmed that λ is not sensitive to the nanoparticles volume fraction (f).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Subsequently, this scaling relationship was generally confirmed in a number of experimental studies and theoretical models [10][11][12][13][14][15], although there was no agreement on the value of power-law exponent (α). The predicted α=0.33 was found [10] to be a reasonable approximation for thin films (L=100 μ), while for the thicker films (L>100 μ) α≈0.5 [9] or even α≈1 [15] were obtained. These studies also confirmed that λ is not sensitive to the nanoparticles volume fraction (f).…”
Section: Introductionmentioning
confidence: 85%
“…Nanoporous materials have been shown to have applications in a number of multidisciplinary fields [1][2][3][4][5][6][7][8][9]. Nanopores with a size ranging from 1 nm to 100 nm have been widely used in recent years as highly sensitive sensors that can detect various molecules, biospecies and nanoparticles in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Moreover, polymer-based nano-objects have the advantage of structural versatility of their components allowing variations in responsive properties, as well as permitting the incorporation of a wide variety of functional end groups. [23][24][25] Polymer nano-compartments serve to create nanoreactors as ideal candidates for the development of reactions at the nanoscale by encapsulation of active molecules inside. 21,26,27 The reactions take place inside the cavities of the compartments, where the active molecules are protected from the environment and perform their activity.…”
Section: Introductionmentioning
confidence: 99%
“…Gating of nanoscale ow-through devices has received major attention in the eld of system engineering for controlled "diffusion" applications, for example in drug-delivery, bioseparation, and sensing applications. [1][2][3][4][5] It is important in such devices that nanochannels are reversibly gated, i.e., they can be switched between an open ("on") and closed ("off") state in response to an external stimulus (e.g. voltage, pH, or temperature variation).…”
Section: Introductionmentioning
confidence: 99%